INVESTIGATION OF DEPORTMENT OF CHALCOPHILIC HEAVY METALS IN THE WASTE ROCK OF CENTRAL COAL ENRICHMENT PLANT "CHERVONOHRADSKA" FOR THE PURPOSES OF ENVIRONMENTAL SAFETY OF LVIV-VOLYN COAL BASIN - Iryna Kochmar; Vasyl Karabyn (Environmental Problems, 2022)
Mining areas are centres of increased environmental danger. This is due to the development and operation of mines and subsequent beneficiation of coal, as well as the storage of significant volumes of empty waste rock in landfills. An important component of ensuring environmental safety is the investigation of the factors and ways of the impact of rock dumps on the state of the environment. In this regard, the article examines the forms of heavy metals found in the rock of the waste heap of the central coal enrichment plant“Chervonohradska”of the Lviv-Volyn coal basin. The environmental hazard factors caused by the distribution of various forms of lead, cadmium, zinc, and copper, based on establishing the migrationcapabilities of these elements in the technogenesis zone, are analyzed. It was determined that the gross content of lead reaches 16.32 mg/kg, cadmium –5.84 mg/kg (exceeding clarke up to 29.2 times in siliceous siltstone and siltstone), zinc –421 mg/kg (exceeding clarke up to 5.26 times in sandstone, siltstone and siliceous siltstone), copper –112.89 mg/kg (exceeding clarke by 2 times in siltstone). The concentration coefficients of heavy metals in the samples were determined in relation to the gross form. The results of the research give a reason to evaluate the rocks of the waste dump in terms of the distribution of various forms of Pb, Cd, Zn and Cu as dangerous for the environment and unsuitable for use because in all the samples an excess content was observed in one form or another.